Notes on Some Economic Texts of the Time of Urukagina - Stephens, Ferris J.
1. Who was Urukagina’s Precedessor? — 2. Lexical Notes — 3. Seizure of Property for Debt — 4. The Date of Urukagina’s Reforms.